2015
DOI: 10.1155/2015/789762
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Bands with Intestinal Malrotation after Propylthiouracil Exposure in Early Pregnancy

Abstract: Exposure to propylthiouracil in early pregnancy may be associated with an increased risk of birth defects. But the spectrum of associated congenital anomalies is not yet well defined. While preliminary reports suggest that most cases of propylthiouracil-associated birth defects are restricted to the preauricular and urinary systems, careful consideration should be given to other possible manifestations of teratogenicity. We propose that congenital bands may potentially represent a rare yet serious complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The present study observed cases of gastrointestinal malformations after PTU exposure. A recent case report described congenital bands with intestinal malrotation in the child after maternal use of PTU in pregnancy (27). Another study described gastrointestinal malformations after exposure to untreated maternal hyperthyroidism (28).…”
Section: Previous Findingsmentioning
confidence: 99%
“…The present study observed cases of gastrointestinal malformations after PTU exposure. A recent case report described congenital bands with intestinal malrotation in the child after maternal use of PTU in pregnancy (27). Another study described gastrointestinal malformations after exposure to untreated maternal hyperthyroidism (28).…”
Section: Previous Findingsmentioning
confidence: 99%
“…PTU is associated with an increase in congenital anomalies less often than MMI/CMZ but some studies have noted an increased risk (Andersen, Lonn, Vestergaard, & Torring, 2017;Andersen, Olsen, Wu, & Laurberg, 2013;Howley et al, 2017;Leung, Yamamoto, Luca, Beaudry, & McKeen, 2015). A case study identified intestinal malrotation with congenital bands (Leung et al, 2015). The child also had a small ventricular septal defect.…”
Section: Propylthioruacilmentioning
confidence: 99%
“…Some authors suggested that congenital anomalies may be related to uncontrolled hyperthyroidism, genetic factors, or a combination of genetics and uncontrolled hyperthyroidism or genetics and antithyroid medications (MMI/CMZ or PTU) rather than the antithyroid medications alone that are used to treat hyperthyroidism (Barbero et al, 2008;Koenig et al, 2010;Leung et al, 2015;Momotani et al, 1984;Momotani & Ito, 1991;Seoud et al, 2003;Stanisstreet et al, 1990;Ting et al, 2013;Van Dijke, Heydendael, & De Kleine, 1987;Yoshihara et al, 2012). However, results from studies including untreated hyperthyroidism are mixed with some studies showing no increased risk (Andersen et al, 2013;Andersen et al, 2017;Korelitz et al, 2013;Lo et al, 2015;Yoshihara et al, 2012) and other studies showing increased risk (Barbero et al, 2008;Momotani et al, 1984;Momotani & Ito, 1991;Seoud et al, 2003;Van Dijke et al, 1987).…”
Section: And Carbinazolementioning
confidence: 99%